Noble Metal Core-Ceria Shell Catalysts For Water-Gas Shift Reaction - Yeung, C; Tsang, S (2009)
The metal - support interface is known to play a key role in many catalysis reactions. Using the microemulsion technique we report the preparation of a nanosized noble metal particle with an intimate contact with cerium oxide. The materials display better catalytic performance in the water - gas shift (WGS) reaction over the hydrogen-rich reformate - steam mixture without methane (side product) formation as compared with catalysts prepared by traditional methods. It is evident that the catalysts prepared by the microemulsion method show an unusual morphology and unique catalytic properties with the noble metal nanoparticle being embedded in a thin layer of cerium oxide, giving a maximum metal - support interface of three-dimensional interactions. In light of results obtained from material characterization as well as reaction rate orders and switching experiment studies over the catalysts, a discussion on possible reaction mechanism(s) taking place at the interface of this new type of catalyst is included in this paper. © 2009 American Chemical Society.